Activation of α7nAChR by Nicotine Reduced the Th17 Response in CD4+T Lymphocytes. (October 2014) - Liu, Zhigang; Han, Bo; Li, Peijie; Wang, Zie; Fan, Qing
<x xml:space="preserve">Abstract</x> Background: nAChRs play an important role in the regulation and modulation of immune cell proliferation, differentiation, migration and cell-cell interactions. The present study was to characterize the expression of α7nAChR on human peripheral blood mononuclear cells (hPBMC) and CD4+T lymphocytes, and to explore the change of Th17 expression after activation of α7nAChR on human CD4+T lymphocytes. Methods: A Ficoll gradient was used to separate hPBMC from whole blood, and then CD4+T lymphocytes were isolated by magnetic bead separation. The expression of α7nAChR on PBMC and CD4+T lymphocytes was analyzed using flow cytometry before and after stimulation with phytohemagglutinin (PHA). The effect of α7nAChR stimulation by nicotine or inhibition by α-bungarotoxin (α-BTX), as well as Th17 expression on the phenotype of CD4+T cells was evaluated using flow cytometric analysis. Results: The percentage of CD4+T cells in reduced PBMC, while the expression of α7nAChR increased when cells were stimulated by nicotine. This effect vanished when co-treated with nicotine and α-BTX. α7nAChR was found to expressed in about 90% of CD4+T cells. However, α7nAChR expression reduced to 80% on CD4+T cells after stimulation with PHA for 24 h. Stimulation of α7nAChR with nicotine increased the expression of Th17 cells, and this upregulation reduced when AChRα7 was inhibited by α-BTX. Conclusion: α7nAChR was ubiquitously expressed by CD4+T lymphocytes, which was correlated with the cell activation status. Meanwhile, activation of nAChRα7 by nicotine in CD4 cells reduced the Th17 response.